Medical students' self-efficacy in problem-based learning and its relationship with self-regulated learning. Issue 1 (1st January 2016) - Demirören, Meral; Turan, Sevgi; Öztuna, Derya
Abstract : Background: Problem-based learning (PBL) is most commonly used in medical education to enhance self-regulated learning (SRL) skills. Self-efficacy beliefs affect students' motivation through self-regulatory processes. The purpose of this study is to examine the relationship between medical students' self-reported SRL skills and their self-efficacy in PBL. Methods: A cross-sectional study was conducted with second (286; 83.1%) and third (275; 80.2%) year students at the Ankara University School of Medicine. The SRL perception (SRLP) scale and self-efficacy for problem-based learning (SPBL) scale were used in the study. Results: The SRLP subscales were positively correlated with the SPBL subscales. There was a weak but meaningful correlation between the subscales of SRLP (with the exception of the lack of self-directedness scale) and the subscales of SPBL and the students' views on benefiting from PBL. The female students' mean score was higher for the 'planning and goal setting' subscale of SRLP ( p= 0.017), and the second-year students' mean score was higher than that of the third-year students for the 'lack of self-directedness' subscale of SRLP ( p= 0.001) with small effect sizes (Cohen's d is 0.17 and 0.27). There was no statistically significant difference between the year and subscales of SPBL. With regard to gender, the female students had higher scores than the male students on the 'responsibility' subscale of SPBL ( p= 0.003; Cohen's d =0.26). Conclusions: The study showed that medical students used SRL skills and believed in their ability to learn effectively in the PBL context and demonstrated the relationship between SRL skills and self-efficacy beliefs. Monitoring students' development in these skills and giving them feedback could be beneficial for the cognitive achievement of students with learning difficulties and insufficient study skills. Further studies need to be undertaken to investigate issues such as the curriculum, learning environment, individual differences, and how these can affect the SRL process.